ПРОФЕСІЙНО-ПЕДАГОГІЧНА ПІДГОТОВКА ВЧИТЕЛЯ НА ПОЛТАВЩИНІ В КІНЦІ ХІХ – НА ПОЧАТКУ ХХ СТ. - Тонконог, Ірина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті здійснено аналіз процесу становлення теоретичного та практичного компонентів професійно-педагогічної підготовки кандидатів на посади вчителів Полтавщини в кінці ХІХ – на початку ХХ ст. Автор досліджує навчальні плани, особливості навчальних програм педагогічних предметів, структуру практики учительських семінарій, жіночих гімназій, учительського інституту в Полтаві, тимчасових педагогічних курсів в зазначений період. Доведено, що професійно-педагогічна підготовка вчителів в регіоні була пов’язана з формуванням змісту освіти. В статье осуществлен анализ процесса становления теоретического и практического компонентов профессионально-педагогической подготовки кандидатов на должности учителей Полтавщины конца ХІХ – начала ХХ в. Автор исследует учебные планы, особенности учебных программ педагогических предметов, структуру практики учительских семинарий, женских гимназий, учительского института в Полтаве, временных педагогических курсов в указанный период. Доказано, что профессионально-педагогическая подготовка учителей в регионе была связана с формированием содержания образования. This article analysed the process of theoretical and practical components of professional pedagogical training of the candidates for teacher ship of Poltavschina in the end of 19-the beginning of 20 century. The author investigates educational plans, peculiarities of educational programmes of pedagogical subjects, the structure of practice of teacher seminaries, women gymnaziums, teacher’s institute in Poltava, temporary pedagogical courses in determined period. On the basis of historical pedagogical analysis we found out the specifics of teacer’s training in Poltavschina in investigaed period. Proved that professional and pedagogical training of teachers in the region was associated with the formation of educational content, which consisted of a common cultural, psychological, pedagogical and general units differ fundamentality teacher training, integration of knowledge in the content of courses, pedagogisation of psychological and educational process ; the desire to increase the level of methodical preparation of the teacher; distribution psychopedagogical training of teaching staff in two directions - theoretical and practical (with a significant advantage in the latter).